TRADISI SEBAMBANGAN PERSPEKTIF MAQASHID AL-SYARIAH DAN HUKUM POSITIF - Alfikrul Akbar; Arief Hanif, Hamdan; Sofyan Munawar (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
The implementation of the Sebambangan Tradition in Kedaton Kalianda Village still often occurs, even some young people often carry out this Sebambangan tradition alone without relatives or a family member interceding, even though it is clear that both of them are not yet mahram, and this Sebambangan practice often occurs without giving any news in the form of letters or entrusted messages through neighbors or close relatives to convey the runaway to the girl's parents, so that the girl's parents are confused because of the lack of news from their children and not infrequently then report it to the police. The results of the study show that based on Maqashid Al-Syari'ah's view, the implementation of Sebambangan in Kedaton Kalianda Village is an act that violates the law and deviates from what has been stated in the Shari'a and the Islamic religion. The form of violation and deviation is because it violates the obligations of a child who must respect, obey and serve both parents. Because of the Sebambangan custom, in practice it is carried away without the permission of both parents. Then also because it violates one's obligation to stay away from adultery which is strictly prohibited by Allah SWT. Because the Sebambangan custom in practice is close to committing adultery. Whereas based on Positive Law in the criminal realm, the practice of Sebambangan is included in a violation of the Criminal Code Article 332 paragraph 1, namely carrying away a girl without the consent of her parents/guardians, but this applies only if there is a complaint of offense by parents to the police only and if there is Complaints can also be resolved by consensus according to applicable customs.